Epigenetic Therapeutics Targeting NRF2/KEAP1 Signaling in Cancer Oxidative Stress - Zhang, Shunhao; Duan, Sining; Xie, Zhuojun; Bao, Wanlin; Xu, Bo; Yang, Wenbin; Zhou, Lingyun (Frontiers in Pharmacology, 2022)
The transcription factor nuclear factor erythroid 2-related factor 2 (NRF2) and its negative regulator kelch-like ECH-associated protein 1 (KEAP1) regulate various genes involved in redox homeostasis, which protects cells from stress conditions such as reactive oxygen species (ROS) and therefore exerts beneficial effects on suppression of carcinogenesis. In addition to their pivotal role in cellular physiology, accumulating innovative studies indicated that NRF2/KEAP1-governed pathways may conversely be oncogenic and cause therapy resistance, which was profoundly modulated by epigenetic mechanism. Therefore, targeting epigenetic regulation in NRF2/KEAP1 signaling is a potential strategy for cancer treatment. In this paper, the current knowledge on the role of NRF2/KEAP1 signaling in cancer oxidative stress is presented, with a focus on how epigenetic modifications might influence cancer initiation and progression. Furthermore, the prospect that epigenetic changes may be used as therapeutic targets for tumor treatment is also investigated.